Prosumer: A new approach to conceptualisation - Myriam Ertz; José María Barragán Maravilla; Xinyuan Cao (Journal of Innovation & Knowledge (JIK), 2025)
The prosumer concept has become increasingly relevant in the current economy, necessitating the development of resilient and adaptive business models. Given the lack of a systematic framework for evaluating prosumers, the present study aimed to develop a framework of reference for assessing the roles and impacts of prosumers across various industries. Although this is not a systematic literature review, 2,500 papers were initially retrieved from the Web of Science and Scopus databases, and 67 were selected and used in the prosumer conceptualisation. CiteSpace software was used to map the prosumer literature stream. The content analysis informed the exploration of the origins of the prosumer concept and the development of a contemporary definition of this concept. Terms that relate to and/or overlap with the prosumer concept, as well as the nuances of prosumer engagement levels, were also analysed. Additionally, prosumers' place in the archetypal sharing economy, as well as their limitations and challenges, were examined. Notably, this study proposes a tentative framework of reference for prosumer conceptualisation and opens up new areas for exploration via a theory-based agenda for future research. This research offers unique contributions to the prosumer literature, practice and other related works because it comprehensively encapsulates and summarises all relevant literature pertaining to the prosumer concept and establishes a transdisciplinary conceptualisation and framework of reference.
Keywords: D11; D16; 650; Prosumer; Economy; Digital economy; Collaborative economy; Co-creation; Sustainable practices